Sistem Pemesanan dan Pembayaran Makanan berbasis Web Terintegrasi dengan Application Programming Interface (API) - Gunawan, Ferry; Bororing, Grace Martha Geertruida (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The era of digitalization makes technology inseparable from human life, such as business people. Business technology in the culinary field such as restaurants, some of which have implemented a food ordering system in the form of digital menus, but still need to queue at the cashier or wait for the waiter to come to take orders. One way to make it easier is to implement a website-based food ordering system where customers can order and pay for their orders directly. The use of this payment method will take advantage of the services of the Xendit API (Application Programming Interface). The technology will be implemented into a web-based application using the Codeigniter framework. This research was conducted using an agile method with a qualitative approach. The research results obtained will be in the form of a web-based application with ordering and payment features that can be done at once. The resulting application is expected to assist cashiers in processing payments, as well as beneficial for customers and business owners because it reduces operational costs.